Superconducting Sr(2-x)A(x)CuO(2)F(2+delta) (A = Ca, Ba): Synthetic pathways and associated structural rearrangements - Francesconi, MG; Slater, P; Hodges, J; Greaves, C; Edwards, P; Al-Mamouri, M; Slaski, M (1998)
The low-temperature fluorination of a range of insulating alkaline earth cuprates Sr2-xAxCuO3 (A = Ca (0 ≤ x ≤ 2); A = Ba (0 ≤ x ≤ 0.6)) can result in superconducting oxide fluorides Sr2-xAxCuO2F2+δ. In contrast, conventional high-temperature solid-state reactions produce thermodynamically more stable mixtures of oxides and fluorides. Various soft-chemistry fluorination pathways (utilizing F2 gas, NH4F, MF2 [M = Cu, Zn, Ni, Ag]) are compared with respect to their efficacy and mechanisms. Attention is also focused on the structural features of the mixed-oxide precursor and the final-oxide fluorides to highlight the remarkable structural rearrangements that occur during the low-temperature fluorination. The effects of fluorination of other Sr-Cu-O systems are used to identify the structural requirements of the precursor oxide in order to achieve such transformations. © 1998 Academic Press.